Cyanobacterial mats and their associated microbiomes in saline and freshwater lakes from the Bolivian Altiplano - Hentschke, Guilherme Scotta; Semedo, Miguel; Ciancas, Jimmy; Hoepfner, Claudia; Guzmán, Daniel; Rivera, Daniela S.; Vasconcelos, Vitor M. (Frontiers in Microbiology, 2025)
The Bolivian Altiplano presents extreme environmental conditions, including high altitude, intense UV radiation, low precipitation, freezing temperatures, and saline to alkaline waters. Despite these harsh settings, cyanobacteria thrive in microbial mats, although their diversity remains poorly characterized. This study aimed to explore the morphological and molecular diversity of cyanobacterial mats and their associated microbiomes in saline and freshwater ecosystems of the Bolivian Altiplano. Morphological analyses revealed seven distinct cyanobacterial morphotypes affiliated with Nostocaceae, Coleofasciculaceae, Rivulariaceae, and Microcoleaceae. Amplicon-based analysis of the 16S rRNA gene identified 4.113 ASV for the bacterial community. Of these, 310 were identified as Cyanobacteria, with 134 classified as Cyanophyceae assigned to 32 genera. Phylogenetic reconstruction and sequence identity comparisons resolved 42 cyanobacterial genera across nine orders. Moreover, 30 ASVs grouped into 16 clades unrelated to any known genus, suggesting the presence of potentially novel cyanobacterial lineages. The microbiome associated with these mats was dominated by Alphaproteobacteria, Bacteroidia, Gammaproteobacteria, Clostridia, Cyanophyceae, and Campylobacteria. Functional predictions based on 16S rRNA gene profiles indicated a predominance of phototrophic and chemoheterotrophic metabolisms, along with sulfur respiration, nitrogen fixation, nitrate and nitrite reduction, and fermentation pathways. Notably, nitrogen-fixing cyanobacteria and bacterial groups with bioremediation potential were prevalent, highlighting the ecological importance and possible biotechnological applications of these microbial consortia. This is the first comprehensive metabarcoding analysis of cyanobacterial mats from Bolivia, including their associated microbiomes. Many new bacterial and cyanobacterial taxa remain to be described in these ecosystems. Based on the functional genomic analysis, this work also highlights the great unexplored biotechnological potential of Bolivia’s extreme environments and the functional roles of microbial mats in biogeochemical cycling under polyextreme conditions.